An experimental study on the influence of an oxygenated additive in diesel engine fuelled with neat papaya seed biodiesel/diesel blends. (15th May 2020) - Devarajan, Yuvarajan; Beemkumar, Nagappan; Ganesan, S.; Arunkumar, T.
Highlights: Potential of papaya seed biodiesel as a partial replacement of diesel has been explored. Oxygenated additives at equal percentage are included to biodiesel to improve the combustion properties of biodiesel/diesel blends. Combustion front such as Heat release rate (HRR) increased with DTBP and decanol content for biodiesel/diesel blends. Performance aspects such as fuel consumption reduced and thermal efficiency enhanced drastically with increase in DTBP and decanol concentration for biodiesel/diesel blends. CO, HC, NOX and smoke emissions decreased linearly with DTBP and decanol addition to biodiesel/diesel blends. Abstract: Poor physical properties of biodiesel (BD100) namely high viscosity and density causes atomization problems leading to higher smoke, HC and CO emissions. The purpose of this work is to enhance the performance aspects and to limit emissions from Papaya seed biodiesel operation. This research paves a way of investing the impact of decanol (n-D) and DTBP on biodiesel/diesel blends on the research engine. Fuel blends employed in these investigations were prepared by altering the volume percentage of Diesel with Papaya seed biodiesel, DTBP, and n-Decanol respectively to prepare three tertiary blends. Diesel is referred to as base fuel with no alteration. Diesel at 50% volume is blended with 50% volume of Papaya seed biodiesel and termed as BD50 (Modified fuel). The modified fuel (BD50) is blended with 10% volume of DTBP and referred as DTBP + BD50 (45% Diesel, 45% BD and 10% DTBP on volume basis). In addition, the modified fuel (BD50) is blended with 10% volume of n-Decanol and referred as n-D + BD50 (45% Diesel, 45% BD and 10% n-D on a volume basis). This work revealed that the performance aspects such as fuel consumption reduced (1.5–2.3%) and thermal efficiency enhanced drastically (0.5–0.8%) with the inclusion of decanol (n-D) and DTBP to BD50. Smoke, HC and CO level decreased for DTBP + BD50, n-D + BD50, and BD50 with a penalty of marginal higher NOX emissions than diesel. Combustion fronts, namely Heat release rate (HRR) and peak pressure increased for BD50 with decanol (n-D) and DTBP inclusion. This research work reveals that 10% of decanol (n-D) and DTBP inclusion in BD50 can optimize diesel engine emissions, combustion, and performance with undergoing any modifications.